The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/pssa.2211350210
|View full text |Cite
|
Sign up to set email alerts
|

Including Thermal Activation in Simulation Calculations of Dislocation Glide

Abstract: Our simulation method which was derived for athermal motion of flexible dislocations through obstacle arrays is extended to include thermally activated glide. The deterministic differential equations which describe the dynamics of dislocation motion get an additional stochastic term corresponding to thermal motion of atoms involved. Our approach is based on publications of Langevin, Fokker‐Planck, and Klein‐Kramers. The investigation of jerky glide reveals that there is an essential influence of the kinetic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Their simulation system focused on two dimensional problems [6,7]. Hiratani and Zbib [8,9] extended the model proposed by Rönnpagel et al [6] to three-dimensional simulations and used it to simulate dislocation glide through weak obstacles which were represented by stacking fault tetrahedra (SFTs). They found that dislocation motion was obstaclecontrolled when the applied stress was below a critical resolved shear stress (CRSS), otherwise drag-controlled [8]; the dislocation line was found to exhibit a self-affine structure as manifested by non-trivial height-difference correlations of dislocation shapes [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their simulation system focused on two dimensional problems [6,7]. Hiratani and Zbib [8,9] extended the model proposed by Rönnpagel et al [6] to three-dimensional simulations and used it to simulate dislocation glide through weak obstacles which were represented by stacking fault tetrahedra (SFTs). They found that dislocation motion was obstaclecontrolled when the applied stress was below a critical resolved shear stress (CRSS), otherwise drag-controlled [8]; the dislocation line was found to exhibit a self-affine structure as manifested by non-trivial height-difference correlations of dislocation shapes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal effects can be considered by incorporating Langevin forces into the equations of motion [6][7][8][9]. Rönnpagel et al [6] developed a stochastic model that considers the effects of temperature in a line tension model within Brownian dynamics scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Then, based on the assumption of the Gaussian process, the thermal stress pulse has zero mean and no correlation [29,30] between the two difference times. This leads to the average peak height given as [9,31] …”
Section: Stochastic Dislocation Dynamicsmentioning
confidence: 99%
“…Therefore, the DD simulation model should also account not only for deterministic effects but also for stochastic forces; leading to a model called "stochastic discrete dislocation dynamics" (SDD) . The procedure is to include the stochastic force Based on the assumption of the Gaussian process, the thermal stress pulse has zero mean and no correlation (Ronnpagel, Streit et al 1993;Raabe 1998) between any two different times.…”
Section: The Stochastic Force and Cross-slipmentioning
confidence: 99%
“…Based on the assumption of the Gaussian process, the thermal stress pulse has zero mean and no correlation (Ronnpagel, Streit et al 1993;Raabe 1998) between any two different times.…”
Section: The Stochastic Force and Cross-slipmentioning
confidence: 99%